How do Australian coaches train fast bowlers? A survey on physical conditioning and workload management practices for training fast bowlers. Issue 5 (October 2018) - Soomro, Najeebullah; Hackett, Daniel; Freeston, Jonathan; Blanch, Peter; Kountouris, Alex; Dipnall, Joanna; Lyle, David; Sanders, Ross
Fast bowlers have the highest injury rates in cricket; therefore, reducing these injuries is a priority for coaches and the support staff. Improving physical conditioning and monitoring bowling workload are primary preventative strategies to reduce overuse injuries. The objective of this study was to investigate practices of cricket coaches in Australia on (1) strength and conditioning and (2) bowling workload management of junior and non-elite fast bowlers. A web-based survey was sent to 548 male Level Two cricket coaches registered with Cricket New South Wales, Australia. One hundred and seventy (31%) coaches responded to the survey. A majority (70%) of the coaches were working with cricketers under the age of 19 years. Only 39 (23%) engaged fast bowlers in resistance training exercises. Coaches under the age of 40 years were more likely to prescribe resistance training (χ 2  = 5.77, df = 1, p = 0.016) than coaches over the age of 40. Lower back, abdominal and gluteal muscles were the most commonly targeted muscle groups. Sit-ups, core work and squats were the most common exercises prescribed. Most (92%) coaches were aware of current national fast bowling workload recommendations. However, only 18 (13%) coaches prescribed the currently recommended workloads. The results indicate that coaches training junior and sub-elite cricketers need more awareness on of the importance of engaging fast bowlers in resistance training and monitoring bowling workloads. Understanding current training practices of coaches can assist in the development of injury prevention programmes for junior fast bowlers and educational programmes for coaches.